An in-vitro Study on the effect of Calotropis Gigantea in different Potencies on Trichophyton Rubrum (Advancements in Homeopathic Research, 2024)
Background: The emergence of resistant fungal  strains due to irrational use of antifungal agents  highlights the need for alternative therapies.  Calotropis gigantea, known for its traditional  medicinal uses, has been explored for its antifungal  properties against Trichophyton rubrum, a common  dermatophyte causing skin infections. Materials and Methods: Standard strains of  T. rubrum (ATCC MYA-029) were cultured on  Sabouraud Dextrose Agar (SDA). Various potencies  of C. gigantea (3X, 6X, 3C, 6C, 12C, 30C, 200C, and  1000C) were evaluated for antifungal activity using  the disc diffusion method. Griseofulvin served as  the positive control, and homeopathic placebo (90%  ethanol) as the negative control. Minimum Inhibitory  Concentration (MIC) values were determined using  turbidometry and analyzed statistically using the  Kruskal-Wallis Test. Results: Lower potencies of C. gigantea (3C,  3X, and 12C) demonstrated significant antifungal  activity, with inhibition zones ranging from 9 ± 0.5  mm to 10 ± 0.3 mm (p < 0.05). MIC50 and MIC90  values for C. gigantea 3C were 100 µL and 200 µL,  respectively, indicating higher efficacy compared to  higher potencies (30C, 200C, and 1000C), which  showed MIC50 and MIC90 values of 500 µL and  900 µL. Griseofulvin exhibited the highest antifungal  activity with MIC50 and MIC90 values of 100 µL  each. The negative control showed no significant  inhibition. Discussion: The antifungal efficacy of C. gigantea is attributed to its bioactive compounds, including  flavonoids and terpenoids. Lower potencies exhibited  stronger activity, aligning with traditional applications  of the plant. The findings support its potential as a  topical antifungal treatment and highlight the value  of MIC in guiding effective dosing strategies. Conclusion: Homeopathic medicine Calotropis  gigantea demonstrates significant antifungal activity,  particularly in lower potencies (3X, 3C, and 12C),  offering a promising alternative for managing  dermatophytic infections. Further research should  focus on optimizing treatment regimens, exploring  synergies with other homeopathic medicines, and  validating findings in clinical settings to address  antifungal resistance effectively.
Keywords: Calotropis gigantea; Trichophyton rubrum; Antifungal activity; Minimum Inhibitory Concentration (MIC); Homeopathic medicine